Performance prediction of a small-sized herringbone-grooved bearing with ferrofluid lubrication considering cavitation - Kao, Yung-Yuan; Chao, Paul C. -P.; Liu, Zong-Bin; Wang, Zhi-Kuan; Liu, Po-Wen; Huang, Jeng-Shen; Chang, Chang-Chun (My University, 2009)
The small-sized herringbone groove journal bearing (HGJB), i. e., so-called "magnetic bearing," filled with Newtonian ferrofluid lubrication is investigated via finite difference analysis (FDA), with consideration of cavitation zones in HGJB. The FDA starts with constructing the mass flux equations of the HGJB filled with ferrofluid. Discretization for FDA is next performed over the bearing clearance domain, from which algebraic finite difference equations based on the mass flow balance over the clearance domain are derived. Solving the equations, rotordynamic coefficients, cavitation zones, and side leakage rate are successfully predicted to show effectiveness in enhancing bearing performance by ferrofluid. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3072771]